Mejora en los procesos de obtención de información de la rentabilidad por cliente de la empresa RIMAC Seguros y Reaseguros S.A. - Sarmiento De La Cruz, John Anderson (2020)
The professional sufficiency plan of this investigation proposes the improvement of the process of obtaining profitability information at the client level in the company RIMAC seguros y reaseguros S.A. For this purpose, it was necessary to present the background of the company, where an analysis of the insurance sector and its position within a highly competitive market was carried out. In this sense, the problems of the company in question addressed the shortcomings in the process of obtaining profitability information at the customer level, which resulted in confidence indicators not representative for management, in addition to not having easily accessible reports for decision making by the management of the finance area. In accordance with this, the solution proposal was developed by identifying the causes that could be assigned to them and establishing priority criteria among them, using industrial engineering tools. The result of the engineering design of the proposed solution contemplated strategies such as the formation of a multidisciplinary team and Scrum to use the agile methodology in the restructuring of technical result (RT) dashboards that fit the needs of its customers.